Long‐term safety, efficacy, and quality of life outcomes with adjunctive brivaracetam treatment at individualized doses in patients with epilepsy: An up to 11‐year, open‐label, follow‐up trial - O’Brien, Terence J.; Borghs, Simon; He, Qin (Jane); Schulz, Anne‐Liv; Yates, Stephen; Biton, Victor (Epilepsia (Copenhagen), 2020)
Objective To evaluate long‐term safety/tolerability of brivaracetam at individualized doses ≤200 mg/d (primary) and maintenance of efficacy over time (secondary) in adults with focal seizures or primary generalized seizures (PGS) enrolled in phase 3, open‐label, long‐term follow‐up trial N01199 (NCT00150800). Methods Patients ≥16 years of age who had completed double‐blind, placebo‐controlled adjunctive brivaracetam trials NCT00175825, NCT00490035, NCT00464269, or NCT00504881 were eligible. Outcomes included safety, efficacy, and quality of life. Results The safety set included 667 patients (focal seizures, 97.8%; PGS, 2.2%); the efficacy set included 648 patients with focal seizures and 15 patients with PGS. Overall, 49.2% of patients had ≥48 months of exposure. Treatment‐emergent adverse events (TEAEs) occurred in 91.2% of all patients (91.3% of focal seizures group), brivaracetam discontinuation due to TEAEs in 14.8%, drug‐related TEAEs in 56.7%, and serious TEAEs in 22.8%. The most common TEAEs in the focal seizures group (≥15%) were headache (25.3%) and dizziness (21.9%). Mean changes from baseline in Hospital Anxiety and Depression Scale scores at last value during 2‐year evaluation were −0.7 (standard deviation [SD] = 4.3) and −0.2 (SD = 4.4) overall. In the focal seizures group, median reduction from baseline in focal seizure frequency/28 days was 57.3%, 50% responder rate was 55.6%, and 6‐month and 12‐month seizure freedom rates were 30.3% and 20.3%, respectively. Efficacy outcomes improved by exposure duration cohort and then stabilized through the 108‐month cohort. Mean improvement from baseline in Patient‐Weighted Quality of Life in Epilepsy Inventory total score (efficacy set) was 5.7 (SD = 16.1, Cohen's d = 0.35) at month 12 and 6.5 (SD = 18.0, Cohen's d = 0.36) at month 24. Significance Adjunctive brivaracetam was well tolerated, with a good safety profile in long‐term use in adults with epilepsy at individualized doses. Approximately half of the patients remained in the trial at 4 years. Brivaracetam reduced focal seizure frequency versus baseline. Efficacy improved with increasing exposure duration and remained stable through the 9‐year cohort.